Implementasi Metode Bahtsul Masail Berbasis Pendidikan Pesantren untuk Meningkatkan Kemampuan Berpikir Kritis dan Kemampuan Menganalisis Peserta Didik pada Pembelajaran Fisika di SMA - Jauharotul Insiyyah; Sri Jumini; Ahmad Khoiri (Universitas Muhammadiyah Purworejo, 2020)
The aims of this study to (1) determine the student ability of critical think and analyze, using the bahtsul masail method, (2) to find out the difference between the bahtsul masail method and the conventional method in physics learning. The method in this study using a true experimental quantitative method with a pretest-posttest control group design. The population used was all class XI students of SMA NU Al-Ma'ruf Kudus and samples were students of class XI MIPA 2 and MIPA 4 taken by random sampling techniques. The data collection used the pretest and posttest to determine the effect of the bahtsul masail method. The results shows (1) The student thinking ability using the Bahtsul Masail method get higher results. (2) Based on the results of data analysis using paired t-test, it is obtained tcount of -7.4828 and ttable of 1.67 with a significance level of 5% and degrees of freedom of 58 so that if t <ttable, then Ho is rejected and Ha is accepted; This means that there is a difference between the mean pretest and posttest scores, there is also a positive and significant relationship between the bahtsul masail model with students' critical thinking and analyzing abilities. The N-gain value is obtained by an average N-gain score of 0.5902 in the medium category. And for the N-gain score obtained an average of 59,023 which is categorized as quite effective. Thus the application of the bahtsul masail method is effective enough to be applied in a lesson.